Co-assembled twisted superstructures formed by disc-bent core amphiphiles. (March 2022) - Gu, Kehua; Yang, Weilu; Wen, Tao; Wang, Qian; Zhang, Wei; Han, Mengying; Shen, Zhihao; Fan, Xinghe; Ho, Rong-Ming
Highlights: Effect of chiral alkyl chain on the self-assembly of disc-bent core shape amphiphiles. Only irregular crystals formed by pure amphiphiles with chiral alkyl chains. Twisted superstructures obtained by co-assembly of chiral amphiphile and achiral one. Abstract: Herein, two asymmetric chiral disc-bent core amphiphiles containing hexa‑ peri -hexabenzocoronene (HBC), R -HBC-BC and S -HBC-BC, were synthesized to study the effects of chiral alkyl chain on the self-assembly of the disc-bent core amphiphiles. Interestingly, instead of forming chiral superstructure, pure R -HBC-BC or S -HBC-BC self-assembled into irregular crystalline texture resulting from the introduction of the chiral alkyl chains. Surprisingly, the formation of helical superstructure can be achieved by co-assembling the chiral disc-bent core amphiphile with achiral HBC-BC, with twisted superstructures having saddle-like curvature observed, which was different from the conventional spiral superstructures. The shape effect on the chirality transfer mechanism from molecule to hierarchical superstructure was thus proposed based on structural analysis of the twisted superstructures. Such interesting morphological transitions among different self-assembled helical morphologies in thin film may provide new insights for the self-assembly of chiral supramolecules. Graphical abstract: Image, graphical abstract